Social mobility and economic development: Evidence from a panel of Latin American regions - Guido Neidhöfer; Matías Ciaschi; Leonardo Gasparini; Joaquín Serrano (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
We explore the role of social mobility as a driver of economic development by constructing a panel data set that includes measures of intergenerational mobility of education at the sub-national level in Latin America. First, we map the geography of educational mobility for 52 Latin American regions, as well as its evolution over time. Then, through a novel weighting procedure that considers the participation of cohorts to the economy in each year, we estimate the effect of changes in mobility on economic indicators, such as income per capita, poverty, child mortality, and luminosity. Hereby, we control for several covariates, including migration, educational expansions, initial conditions, and unobserved cross-regional heterogeneity. Our findings show that increasing social mobility had a significant and robust impact on the development of Latin American regions.
Keywords: D63; I24; J62; O15; 330; Intergenerational Mobility; Equality of Opportunity; Development; Growth; Latin America